Electrochemiluminescence methods using CdS quantum dots in aptamer-based thrombin biosensors: a comparative study - Isildak, Ibrahim; Navaeipour, Farzaneh; Afsharan, Hadi; Kanberoglu, Gulsah Soydan; Agir, Ismail; Ozer, Tugba; Annabi, Nasim; Totu, Eugenia Eftimie; Khalilzadeh, Balal (SPRINGER WIEN, 2020)
The detection of thrombin by using CdS nanocrystals (CdS NCs), gold nanoparticles (AuNPs) and luminol is investigated in this work. Thrombin is detected by three methods. One is called the quenching method. It is based on the quenching effect of AuNPs on the yellow fluorescence of CdS NCs (with excitation/emission wavelengths of 355/550 nm) when placed adjacent to CdS NCs. The second method (called amplification method) is based on an amplification mechanism in which the plasmonics on the AuNPs enhance the emission of CdS NCs through distance related Forster resonance energy transfer (FRET). The third method is ratiometric and based on the emission by two luminophores, viz. CdS NCs and luminol. In this method, by increasing the concentration of thrombin, the intensity of CdS NCs decreases, while that of luminol increases. The results showed that ratiometric method was most sensitive (with an LOD of 500 fg.mL(-1)), followed by the amplification method (6.5 pg.mL(-1)) and the quenching method (92 pg.mL(-1)). Hence, the latter is less useful.
Keywords: CdS Nanocrystals; Gold nanoparticles; Ratiometric biosensor; Thrombin; Aptamer; Electrochemiluminescence; SIGNAL AMPLIFICATION; CASPASE-3 ACTIVITY; MOLECULAR BEACON; APTASENSOR; CANCER; OXIDE; QUANTIFICATION; NANOPARTICLES; IMMUNOSENSOR; ELECTRODE; Chemistry